Pilot-scale experimental test on gas production from methane hydrate decomposition using depressurization assisted with heat stimulation below quadruple point - Wang, Yi; Feng, Jing-Chun; Li, Xiao-Sen (International Journal of Heat and Mass Transfer, 2019)
Natural gas hydrate can be regarded as alternative energy source in future. Therefore, developing approaches for enhancing gas recovery from hydrate reservoir is attracting extensive attention. A Pilot-Scale Hydrate Simulator (PHS) with the effective volume of 117.8 L was applied for investigating gas recovery from hydrate dissociation below quadruple point in porous media, where hydrate exists with ice, water, and methane gas. Depressurization and depressurization assisted with heat stimulation below quadruple point were selected as the hydrate decomposition method. The influence of heat stimulation on hydrate decomposition below quadruple point was evaluated. The experimental results indicate that the hydrate decomposition rate can be greatly enhanced by decreasing the pressure below quadruple point, because ice can be generated during hydrate decomposition below quadruple point. Heat released by ice formation can immediately supply to hydrate decomposition. During hydrate decomposition experiment by depressurization assisted with heat stimulation, the influence of heat stimulation on hydrate recovery below quadruple point is not obviously, because injected heat is used for ice melting rather than hydrate dissociation. Therefore, heat stimulation may not enhance hydrate dissociation below quadruple point. (C) 2018 Elsevier Ltd. All rights reserved.